A history of detachable coils: 1987–2012. (13th February 2013) - Hui, Ferdinand K; Fiorella, David; Masaryk, Thomas J; Rasmussen, Peter A; Dion, Jacques E
Abstract : Background: The development of detachable coils is one of the most pivotal developments in neurointervention, providing a tool that could be used to treat a wide variety of hemorrhagic stroke. From the original Guglielmi detachable coil, a number of different coil designs and delivery designs have evolved. This article reviews the history of commercially available detachable coils. Methods: A timeline of detachable coils was constructed and coil design philosophies were reviewed. Results: A complete list of commercially available coils is presented in a timeline format. Conclusions: Detachable coil technology continues to evolve. Advances in construction and design have yielded products which may benefit patients in terms of safety, radiation dose reduction and cost of treatment. Continued evolution is expected, irrespective of competing disruptive technologies.